Differential modulation of resistance biomarkers in skin of juvenile and mature pink salmon, Oncorhynchus gorbuscha by the salmon louse, Lepeophtheirus salmonis. Issue 1 (November 2015) - Braden, Laura M.; Barker, Duane E.; Koop, Ben F.; Jones, Simon R.M.
Abstract: Juvenile pink salmon larger than 0.7 g reject the sea louse, Lepeophtheirus salmonis, and are considered resistant to the infection. Robust innate defense responses in the skin contribute to the observed resistance. In contrast adult pink salmon captured at sea or shortly before spawning carry large numbers of the parasite, suggesting inability to control the infection. The purpose of this research is to better understand these apparently contradictory conclusions by comparing a suite of genetic and cellular markers of resistance to L. salmonis in the skin of juvenile and mature pink salmon. The expression of major histocompatibility factor II, C-reactive protein, interleukin-1β, interleukin-8 and cyclooxygenase-2 was down-regulated in mature but not juvenile pink salmon. Similarly, skin at the site of parasite attachment in juvenile salmon was highly populated with MHIIβ + and IL-1β + cells that were either absent, or at reduced levels at similar sites in mature salmon. In addition, mucocyte density was relatively low in the skin of mature salmon, irrespective of louse infection. In juveniles, the higher mucocyte density decreased following louse attachment. We show that in mature pink salmon, genetic and histological responses in skin are depressed and speculate that salmonid defense against L. salmonis is modulated by maturation. Highlights: Cytological and transcriptomic responses to salmon lice in skin of juvenile and mature pink salmon are compared. Fewer mucocytes and cells bearing MHIIβ and IL-1β markers and reduced innate immune gene expression occurred in mature pink salmon. Energy partitioning between defense and other functions during aging is discussed.